THE INFLUENCE OF THE MIND MAPPING LEARNING MODEL TO INCREASE LEARNING OUTCOMES IN SOCIAL SCIENCE SUBJECTS - Rokmanah, Siti; Nurma'ardi, Hilda Dhaniartika; Oktaviani, Anna Maria (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
AbstractThis research is motivated by the students’ low interest and learning outcomes in Social Studies subjects. This research aims to determine and analyze student learning outcomes in the 5th grade Social Studies subjects at SD Negeri Kragilan 1 on the material of the Struggle to Prepare for Indonesia’s Independence using the mind mapping learning model. This research uses a quasi-experimental method with the hypothesis that the improvement of students’ Social Studies learning outcomes using the mind mapping learning model is better than students with conventional learning models. The results of the pretest test data are normally distributed and homogeneous; in the hypothesis test, the results are -3.0110 < 1.67155, which means that H0 is accepted. After giving treatment to the experimental and control class, then post-test was carried out. The results of the post-test data are normally distributed and homogeneous, while the hypothesis test results are 2.1238 > 1.67155, which means that H1 is accepted. The analysis of student learning outcomes improvement in Social Studies learning uses the N-Gain test, with the results of the N-Gain test calculation for the experimental class getting an average of 65, while the control class is 47. In the hypothesis test, the results obtained 98.59 > 1.645, which means H1 is accepted. It shows that the use of the mind mapping learning model affects increasing student learning outcomes in the Social Sciences subjects.Keywords: Mind Mapping; Learning Outcomes; Social Studies